3D printed artificial marble and preparation method thereof
Through 3D printing technology and photocuring methods, combined with specific raw materials and proportions, the problem of insufficient curing speed and mechanical properties of artificial marble is solved, high-simulation patterns and textures are achieved, and the toughness, strength and wear resistance of the material are significantly improved.
Patent Information
- Application Number
- CN202510083968.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
AI Technical Summary
The existing artificial marble has shortcomings in curing speed and mechanical properties, and the patterns are prone to falling off.
Artificial marble is prepared by 3D printing technology and photocuring methods, and the patterns and textures with instant curing and high simulation are achieved by using raw materials such as acrylic monomers, polyurethane acrylates, inorganic fillers, coupling agents, wetting and dispersing agents, toughening agents, pigments and photoinitiators by reasonably controlling the proportion of raw materials and 3D printing parameters.
It significantly improves the toughness, strength and wear resistance of artificial marble, reduces the linear thermal expansion coefficient and water absorption, and ensures the long-term stability and decorative effect of the pattern.
Smart Images

Figure BDA0005249569940000071 
Figure BDA0005249569940000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of artificial marble, and in particular to 3D printed artificial marble and a preparation method thereof. Background Art
[0002] Since the veins of natural stone are natural, it is difficult to achieve repeatability between batches. In terms of decoration, due to the high hardness and poor plasticity of natural stone, it cannot be made into curved shapes. The existing artificial stone marble patterns and designs are mainly natural or carved to form grooves, which are then filled with artificial stone. After grinding the excess material on the surface, patterns and designs are formed in the grooves. Since the filled patterns are not cast and solidified as a whole with the board surface, after a certain period of time, due to the relatively high proportion of resin in the pattern material, the shrinkage of the two is inconsistent, and the pattern will fall off.
[0003] Compared with natural marble, artificial marble has better wear resistance, acid resistance, high temperature resistance, pressure resistance, flexural resistance, and penetration resistance. It is easy to cut and process, and can be seamlessly bonded at any length. It makes up for the defects of traditional natural marble, such as insufficient elasticity and easy to break, difficult to clean after being stained with dirt, inconvenient to repair after being broken and scratched, and the processable length is too short to be made into an integral countertop. It has good physical properties and decorative sense. It is now widely used in ceilings, walls, floor paving, bathroom vanities, kitchen cabinets and other interior decorations. Polyester artificial marble is the most common, however, polyester artificial marble has relatively poor weather resistance and heat resistance, and is difficult to be thermoformed. Artificial marble prepared from acrylic resin has many advantages, such as good appearance, elegant color, good weather resistance, good processing performance, light weight and high strength, and is widely used in many fields. Artificial marble made of acrylic resin is usually prepared by the following method: filler is mixed into the resin slurry mixture, cast with a forming mold or a continuous steel belt, and the resulting product is hardened. It has the defects of slow curing speed and poor mechanical properties.
[0004] Therefore, it is of great value to provide a 3D printed artificial marble suitable for preparing various textures and colors, with fast curing speed and good mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to provide a 3D printed artificial marble and a preparation method thereof in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a 3D printed artificial marble, comprising the following raw materials in parts by weight: 40-45 parts of acrylic monomer, 10-20 parts of polyurethane acrylate, 50-60 parts of inorganic filler, 0.5-1.5 parts of coupling agent, 0.5-2 parts of wetting dispersant, 5-10 parts of toughening agent, 0.5-1.5 parts of pigment, and 1-3 parts of photoinitiator;
[0008] The acrylic monomer comprises one or more of methyl methacrylate, tetrahydrofuran methacrylate, isobornyl methacrylate, isooctyl methacrylate, lauryl methacrylate and dicyclopentenyl methacrylate.
[0009] Preferably, the inorganic filler comprises one or more of calcium aluminate, barium sulfate, silicon dioxide, aluminum oxide and sodium feldspar, and the specific gravity of the inorganic filler is 2.5 to 8 g / cm 3 , the particle size of the inorganic filler is 20 to 50 μm.
[0010] Preferably, the coupling agent comprises one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.
[0011] Preferably, the toughening agent is one or more of illite, styrene-butadiene rubber, polyamide rubber, acrylonitrile-butadiene-styrene copolymer, silicone rubber, siloxane polymer, nano-silicon and nano-clay.
[0012] Preferably, the pigment comprises one or more of chrome yellow, iron yellow, medium yellow, iron blue, phthalocyanine blue, iron red, cadmium red and cadmium yellow.
[0013] Preferably, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or 1-hydroxycyclohexyl phenyl ketone.
[0014] The present invention also provides a method for preparing the 3D printed artificial marble, comprising the following steps:
[0015] 1) mixing methyl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting and dispersing agent, toughening agent, pigment and photoinitiator to obtain a mixture;
[0016] 2) According to the natural marble image or artificial marble model, the mixture is 3D printed and light-cured at the same time to obtain artificial marble with the desired pattern and texture.
[0017] Preferably, the mixing time in step 1) is 10 to 20 minutes, and the mixing is carried out at a rotation speed of 500 to 1000 r / min.
[0018] Preferably, the light source for the 3D printing in step 2) is a high-pressure mercury lamp, and the 3D printing and light curing are performed at room temperature.
[0019] The beneficial effects of the present invention include the following:
[0020] 1) Acrylic monomers have the advantages of strong adhesion, excellent weather resistance, chemical corrosion resistance, etc. Polyurethane acrylate has high abrasion resistance, flexibility, good tear strength, excellent optical properties and weather resistance, which combines the excellent properties of polyurethane and acrylate. Tougheners have high impact strength on vertical surfaces, which can effectively improve the fracture strength and toughness of artificial marble. The addition of pigments and inorganic fillers makes the color and morphology of artificial marble closer to natural stone.
[0021] 2) The present invention rationally selects various raw materials, controls the proportion of the raw materials, and obtains artificial marble that is instantly cured and has no significant difference in morphology and color from natural marble through 3D printing technology and light curing. The artificial marble of the present invention has significantly improved toughness, strength and wear resistance, and significantly reduced linear thermal expansion coefficient and water absorption rate. DETAILED DESCRIPTION
[0022] The present invention provides a 3D printed artificial marble, comprising the following raw materials in parts by weight: 40-45 parts of acrylic monomer, 10-20 parts of polyurethane acrylate, 50-60 parts of inorganic filler, 0.5-1.5 parts of coupling agent, 0.5-2 parts of wetting dispersant, 5-10 parts of toughening agent, 0.5-1.5 parts of pigment, and 1-3 parts of photoinitiator;
[0023] The acrylic monomer comprises one or more of methyl methacrylate, tetrahydrofuran methacrylate, isobornyl methacrylate, isooctyl methacrylate, lauryl methacrylate and dicyclopentenyl methacrylate.
[0024] The 3D printed artificial marble of the present invention contains 40 to 45 parts of acrylic acid monomer, preferably 41 to 44 parts, and more preferably 42 to 43 parts.
[0025] The 3D printed artificial marble of the present invention contains 10 to 20 parts of polyurethane acrylate, preferably 12 to 17 parts, and more preferably 14 to 15 parts.
[0026] In the present invention, the polyurethane acrylate is preferably Laromer UA 9154 Aqua polyurethane acrylate or Laromer LR 9004 polyurethane acrylate.
[0027] The 3D printed artificial marble of the present invention contains 50 to 60 parts of inorganic filler, preferably 52 to 58 parts, and more preferably 55 to 56 parts.
[0028] In the present invention, the inorganic filler preferably comprises one or more of calcium aluminate, barium sulfate, silicon dioxide, aluminum oxide and sodium feldspar, and the specific gravity of the inorganic filler is preferably 2.5 to 8 g / cm 3 , more preferably 4 to 6 g / cm 3 ; The particle size of the inorganic filler is preferably 20 to 50 μm, and more preferably 30 to 40 μm.
[0029] In the present invention, if the particle size of the inorganic filler is too small, the light transmittance of the artificial marble is poor; if the particle size of the inorganic filler is too large, the physical properties of the artificial marble are reduced; if the amount of the inorganic filler is too small, there will be a loss of color tone, a decrease in strength and deterioration of texture; if the amount of the inorganic filler is too large, the processability will be reduced, the viscosity will increase, and the curing rate will be reduced.
[0030] The 3D printed artificial marble of the present invention contains 0.5 to 1.5 parts of coupling agent, preferably 0.8 to 1.2 parts, and more preferably 1 part.
[0031] In the present invention, the coupling agent preferably comprises one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent; the titanate coupling agent is preferably a titanate coupling agent YB-301 or a titanate coupling agent LICA 38; the silane coupling agent is preferably vinyl trimethoxy silane or γ-methacryloxypropyl trimethoxy silane (silane coupling agent KH-570); the aluminate coupling agent is preferably aluminate coupling agent A-1160 or aluminate coupling agent DL-411.
[0032] The 3D printed artificial marble of the present invention contains 0.5 to 2 parts of a wetting and dispersing agent, preferably 0.8 to 1.6 parts, and more preferably 1 to 1.5 parts; the wetting and dispersing agent is preferably AFCONA-7520 wetting and dispersing agent or BYK-W909 wetting and dispersing agent.
[0033] The 3D printed artificial marble of the present invention contains 5 to 10 parts of a toughening agent, preferably 6 to 9 parts, and more preferably 7 to 8 parts; the toughening agent is preferably one or more of illite, styrene-butadiene rubber, polyamide rubber, acrylonitrile-butadiene-styrene copolymer, silicone rubber, siloxane polymer, nano-silicon and nano-clay.
[0034] The 3D printed artificial marble of the present invention contains 0.5 to 1.5 parts of pigment, preferably 0.8 to 1.2 parts, and more preferably 1 part; the pigment preferably contains one or more of chrome yellow, iron yellow, medium yellow, iron blue, phthalocyanine blue, iron red, cadmium red and cadmium yellow.
[0035] The 3D printed artificial marble of the present invention contains 1 to 3 parts of a photoinitiator, preferably 1.5 to 2.5 parts, and more preferably 2 parts; the photoinitiator is preferably 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) and / or 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184).
[0036] The present invention also provides a method for preparing the 3D printed artificial marble, comprising the following steps:
[0037] 1) mixing methyl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting and dispersing agent, toughening agent, pigment and photoinitiator to obtain a mixture;
[0038] 2) According to the natural marble image or artificial marble model, the mixture is 3D printed and light-cured at the same time to obtain artificial marble with the desired pattern and texture.
[0039] In the present invention, the mixing time in step 1) is preferably 10 to 20 min, more preferably 12 to 18 min, and more preferably 15 to 16 min; the mixing is preferably carried out at a rotation speed of 500 to 1000 r / min, more preferably 600 to 900 r / min, and more preferably 700 to 800 r / min.
[0040] In the present invention, the mixture is refined before 3D printing, and the particle size of the mixture after the refinement is preferably 5 to 25 μm, and more preferably 10 to 20 μm.
[0041] In the present invention, the light source for the 3D printing in step 2) is preferably a high-pressure mercury lamp, and the 3D printing and light curing are performed at room temperature.
[0042] In the present invention, during the 3D printing process, the moving speed of the mixed material is preferably 2 to 3 cm / s, more preferably 2.2 to 2.8 cm / s, and more preferably 2.5 to 2.6 cm / s.
[0043] In the present invention, pigments having three colors of red, yellow and blue are combined with other raw materials to obtain acrylic mixtures of three colors. The acrylic mixture is cured layer by layer during 3D printing, and the curing is completed within 1 to 2 seconds to obtain the target marble material.
[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] In the embodiment, the scanning accuracy of scanning and recording the target marble image is 0.08mm, and the accurate color gamut discrimination range is above level 8; the ultraviolet light curing adopts a high-pressure mercury lamp with an output power of 125W and a spectrum output of 300-400nm.
[0046] Example 1
[0047] 3D printed artificial marble is made of the following raw materials in parts by weight: 30 parts of methyl methacrylate, 13 parts of isooctyl methacrylate, 15 parts of polyurethane acrylate, 55 parts of inorganic filler, 1 part of coupling agent, 1.2 parts of wetting and dispersing agent, 7 parts of toughening agent, 1 part of pigment, and 2 parts of photoinitiator; the polyurethane acrylate is Laromer UA 9154 Aqua polyurethane acrylate, the inorganic filler is barium sulfate and aluminum oxide in a mass ratio of 2:1, and the specific gravity of the inorganic filler is 5 g / cm 3 , particle size is 30-40μm; the coupling agent is silane coupling agent KH-570, the wetting and dispersing agent is AFCONA-7520 wetting and dispersing agent, the toughening agent is nano silicon and illite in a mass ratio of 1:1, the pigment is iron red, iron blue and cadmium yellow in a mass ratio of 1:1:1, and the photoinitiator is photoinitiator 1173 and photoinitiator 184 in a mass ratio of 3:1.
[0048] Methyl methacrylate, isooctyl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting dispersant, toughening agent, pigment and photoinitiator were mixed at a rotation speed of 800 r / min for 15 minutes and then ground to obtain a mixture with a particle size of 10 μm.
[0049] The target marble image (natural marble image) is drawn into a CAD three-dimensional image, and the marble image is scanned and recorded in the 3D printer. After adding the mixture into the material cavity, 3D printing is performed at room temperature. During the 3D printing process, the movement speed of the mixture is 2.5 cm / s. 3D printing is simultaneously performed at room temperature for UV curing for 1 second to obtain 3D printed artificial marble.
[0050] The 3D printed artificial marble of this embodiment has clear concave-convex textures and good decorative effects. The pattern and texture are highly simulated with the target marble image, and the 3D printed artificial marble can be cured instantly.
[0051] Example 2
[0052] 3D printed artificial marble is made of the following raw materials in parts by weight: 40 parts of isobornyl methacrylate, 18 parts of polyurethane acrylate, 60 parts of inorganic filler, 0.8 parts of coupling agent, 0.8 parts of wetting and dispersing agent, 6 parts of toughening agent, 1.2 parts of pigment, and 1.5 parts of photoinitiator; the polyurethane acrylate is Laromer LR 9004 polyurethane acrylate, the inorganic filler is silicon dioxide and calcium aluminate in a mass ratio of 1:1, and the specific gravity of the inorganic filler is 4 g / cm 3, particle size is 25-35μm; the coupling agent is titanate coupling agent YB-301, the wetting and dispersing agent is BYK-W909 wetting and dispersing agent, the toughening agent is styrene-butadiene rubber (weight average molecular weight 400,000-500,000), the pigments are chrome yellow, phthalocyanine blue and iron red in a mass ratio of 2:1:1, and the photoinitiator is photoinitiator 1173.
[0053] Isobornyl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting dispersant, toughening agent, pigment and photoinitiator were mixed at a rotation speed of 600 r / min for 20 minutes and then ground to obtain a mixture with a particle size of 20 μm.
[0054] The target marble image (artificial marble image) is drawn into a CAD three-dimensional image, and the marble image is scanned and recorded in the 3D printer. After adding the mixture into the material cavity, 3D printing is performed at room temperature. During the 3D printing process, the movement speed of the mixture is 2.2 cm / s. 3D printing is simultaneously performed at room temperature for UV curing, which lasts for 1.5 seconds to obtain 3D printed artificial marble.
[0055] The 3D printed artificial marble of this embodiment has clear concave-convex textures and good decorative effects. The pattern and texture are highly simulated with the target marble image, and the 3D printed artificial marble can be cured instantly.
[0056] Example 3
[0057] 3D printed artificial marble is made of the following raw materials in parts by weight: 45 parts of lauryl methacrylate, 10 parts of polyurethane acrylate, 50 parts of inorganic filler, 1.2 parts of coupling agent, 1.6 parts of wetting and dispersing agent, 9 parts of toughening agent, 0.8 parts of pigment, and 2.5 parts of photoinitiator; the polyurethane acrylate is Laromer UA 9154Aqua polyurethane acrylate, the inorganic filler is barium sulfate, aluminum oxide and sodium feldspar in a mass ratio of 1:1:1, and the specific gravity of the inorganic filler is 6g / cm 3 , particle size is 30-40μm; the coupling agent is aluminate coupling agent A-1160, the wetting and dispersing agent is AFCONA-7520 wetting and dispersing agent, the toughening agent is acrylonitrile-butadiene-styrene copolymer, the pigments are cadmium red, iron blue and medium yellow in a mass ratio of 1:1:1, and the photoinitiator is photoinitiator 184.
[0058] Lauryl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting dispersant, toughening agent, pigment and photoinitiator were mixed at a rotation speed of 900 r / min for 10 minutes and then ground to obtain a mixture with a particle size of 12 μm.
[0059] The target marble image (natural marble image) is drawn into a CAD three-dimensional image, and the marble image is scanned and recorded in the 3D printer. After adding the mixture into the material cavity, 3D printing is performed at room temperature. During the 3D printing process, the movement speed of the mixture is 2.8 cm / s. 3D printing is simultaneously performed at room temperature for UV curing for 1 second to obtain 3D printed artificial marble.
[0060] The 3D printed artificial marble of this embodiment has clear concave-convex textures and good decorative effects. The pattern and texture are highly simulated with the target marble image, and the 3D printed artificial marble can be cured instantly.
[0061] Comparative Example 1
[0062] The toughening agent in Example 1 was omitted, the particle size of the inorganic filler was 10 μm, the laser beam temperature was 1500° C., the moving speed of the mixture was 1 cm / s, and the other conditions were the same as in Example 1.
[0063] Comparative Example 2
[0064] The polyurethane acrylate and wetting dispersant in Example 1 were omitted, the inorganic filler was 80 parts, the methacrylate was 20 parts, and the other conditions were the same as in Example 1.
[0065] The performance tests were conducted on the artificial marbles prepared in Examples 1 to 3 and Comparative Examples 1 to 2. The impact toughness was determined by referring to GB / T1732-2003 "Test Method for Impact Resistance of Paint Films", and the surface was observed for cracks, wrinkles and peeling. The wear resistance, compression strength, linear thermal expansion coefficient and water absorption rate were determined by referring to DB44 / T768-2010 "Resin-based Artificial Marble Plates". The test results are shown in Table 1.
[0066] Table 1 Performance test results of artificial marble of embodiment and comparative example
[0067]
[0068]
[0069] The present invention uses 3D printing technology to prepare artificial marble with concave-convex texture, various colors, and appearance very similar to natural marble by reasonably selecting raw materials and controlling the amount of each raw material. The artificial marble has good decorative effect. The 3D printing of the present invention can achieve a "what you see is what you get" image effect, and the processing method is simple. The method of the present invention significantly improves the toughness, strength and wear resistance of the artificial marble, and significantly reduces the linear thermal expansion coefficient and water absorption rate.
[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A 3D printed artificial marble, characterized in that: The invention comprises the following raw materials in parts by weight: 40-45 parts of acrylic monomer, 10-20 parts of polyurethane acrylate, 50-60 parts of inorganic filler, 0.5-1.5 parts of coupling agent, 0.5-2 parts of wetting dispersant, 5-10 parts of toughening agent, 0.5-1.5 parts of pigment, and 1-3 parts of photoinitiator; The acrylic monomer comprises one or more of methyl methacrylate, tetrahydrofuran methacrylate, isobornyl methacrylate, isooctyl methacrylate, lauryl methacrylate and dicyclopentenyl methacrylate.
2. The 3D printed artificial marble according to claim 1, characterized in that: The inorganic filler comprises one or more of calcium aluminate, barium sulfate, silicon dioxide, aluminum oxide and sodium feldspar, and the specific gravity of the inorganic filler is 2.5-8 g / cm 3 , the particle size of the inorganic filler is 20 to 50 μm.
3. The 3D printed artificial marble according to claim 1 or 2, characterized in that: The coupling agent comprises one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.
4. The 3D printed artificial marble according to claim 3, characterized in that: The toughening agent is one or more of illite, styrene-butadiene rubber, polyamide rubber, acrylonitrile-butadiene-styrene copolymer, silicone rubber, siloxane polymer, nano-silicon and nano-clay.
5. The 3D printed artificial marble according to claim 4, characterized in that: The pigment comprises one or more of chrome yellow, iron yellow, medium yellow, iron blue, phthalocyanine blue, iron red, cadmium red and cadmium yellow.
6. The 3D printed artificial marble according to claim 4 or 5, characterized in that: The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or 1-hydroxycyclohexyl phenyl ketone.
7. The method for preparing 3D printed artificial marble according to any one of claims 1 to 6, characterized in that: The following steps are included: 1) mixing methyl methacrylate, polyurethane acrylate, inorganic filler, coupling agent, wetting and dispersing agent, toughening agent, pigment and photoinitiator to obtain a mixture; 2) According to the natural marble image or artificial marble model, the mixture is 3D printed and light-cured at the same time to obtain artificial marble with the desired pattern and texture.
8. The preparation method according to claim 7, characterized in that: The mixing time of step 1) is 10 to 20 minutes, and the mixing is carried out at a rotation speed of 500 to 1000 r / min.
9. The preparation method according to claim 7 or 8, characterized in that: Step 2) The light source for 3D printing is a high-pressure mercury lamp, and 3D printing and light curing are performed at room temperature.
Citation Information
Cited By
Artificial marble and preparation method thereof
CN121135334A